In-situ preparation of nitrogen-doped unimodal ultramicropore carbon nanosheets with ultrahigh gas selectivity. (August 2019) - Fu, Ning; Yu, Jing; Zhao, Jing; Liu, Rui; Li, Feng; Du, Yuchuan; Yang, Zhenglong
Abstract: The development of simple and feasible methods to synthesize highly efficient adsorbents is the key to low-cost gas purification. Here we developed an in-situ amorphous cobalt template method based on the synergistic effect of precursor to synthesize nitrogen doped unimodal ultramicropores carbon nanosheets Co-NDPCs with high nitrogen content (up to 11.74%), large specific surface area (up to 1187 m 2  g −1 ) and unimodal ultramicropore. As an adsorbent, the Co-NDPCs exhibit unprecedented C2 H2, C2 H6, C3 H8 and CO2 uptake capacities of 6.7, 5.9, 7.4 and 5.6 mmol g −1, respectively, and the corresponding x/CH4 and CO2 /N2 IAST selectivities are as high as 75.3, 65.9.1743.6, 11.4 and 74.7 at 298 K and 1 bar. More importantly, this method effectively avoids the defects of traditional activation or template method, such as corrosiveness, poor safety and complicated process, indicating that Co-NDPCs is a promising adsorbent for CH4 /C2 H2 /C2 H6 /C3 H8 /CO2 /N2 capture and separation. Graphical abstract: Image 1